Mass Ratio Distribution of Hierarchical Triple Systems from the LAMOST-MRS Survey - Tongyu He; Jiangdan Li; Xuefei Chen; Rong-jia Yang; Lin Xiao; Zhanwen Han (The Astrophysical Journal, 2023)
Hierarchical triple-star systems consists of three components organized into an inner binary ( M _1 , M _2 ) and a more distant outer tertiary ( M _3 ) star. The LAMOST Medium-Resolution Spectroscopic Survey has offered a great sample for the study of triple-system populations. We used the peak amplitude ratio method to obtain the mass ratio ( q _in , q _out ) of a triple system from its normalized spectrum. By calculating the cross-correlation function, we determined the correlation between the mass ratio q _out ( M _3 /( M _1 + M _2 )) and the amplitude ratio ( A _3 /( A _1 + A _2 )). We derived a q _in of 0.5–1.0 and a q _out between 0.2 and 0.8. By fitting a power-law function of the corrected q _in distribution, γ _in is estimated to be −0.654 ± 2.915, 4.304 ± 1.125, and 11.371 ± 1.309 for A-, F-, and G-type stars. The derived γ _in values increase as the mass decreases, indicating that less massive stars are more likely to have companion stars with similar masses. By fitting a power-law function of the corrected q _out distribution, γ _out is estimated to be −2.016 ± 0.172, −1.962 ± 0.853, and −1.238 ± 0.141 for G-, F-, and A-type stars, respectively. The γ _out values show a trend of growth toward lower primary star masses.